Ultralow‐Temperature Li/CFx Batteries Enabled by Fast‐Transport and Anion‐Pairing Liquefied Gas Electrolytes. Issue 3 (8th December 2022) - Yin, Yijie; Holoubek, John; Liu, Alex; Sayahpour, Baharak; Raghavendran, Ganesh; Cai, Guorui; Han, Bing; Mayer, Matthew; Schorr, Noah B.; Lambert, Timothy N.; Harrison, Katharine L.; Li, Weikang; et al.
Abstract: Lithium fluorinated‐carbon (Li/CF x ) is one of the most promising chemistries for high‐energy‐density primary energy‐storage systems in applications where rechargeability is not required. Though Li/CF x demonstrates high energy density (>2100 Wh kg −1 ) under ambient conditions, achieving such a high energy density when exposed to subzero temperatures remains a challenge, particularly under high current density. Here, a liquefied gas electrolyte with an anion‐pair solvation structure based on dimethyl ether with a low melting point (−141 °C) and low viscosity (0.12 mPa s, 20 °C), leading to high ionic conductivity (>3.5 mS cm −1 ) between −70 and 60 °C is reported. Besides that, through systematic X‐ray photoelectron spectroscopy integrated with transmission electron microscopy characterizations, the interface of CF x is evaluated for low‐temperature performance. The fast transport and anion‐pairing solvation structure of the electrolyte are concluded to bring about reduced charge‐transfer resistance at low temperatures, which results in significantly enhanced performance of Li/CF x cells (1690 Wh kg −1, −60 °C based on active materials). Utilizing 50 mg cm −2 loading electrodes, the Li/CF x still displays 1530 Wh kg −1 at −60 °C. This work provides insights into the electrolyte design that may overcome the operational limits of batteries in extreme environments. Abstract : Primary batteries serve as indispensable power sources for hard‐to‐reach places or when recharging is unnecessary. A Li/CF x  primary battery with practical loading is developed to provide high energy density down to −70 °C, which is enabled by a liquefied gas electrolyte providing fast transport and anion‐pairing. These design principles are of high interest to similar battery systems operating under extreme conditions.